Anatomy, histology, and morphology of fish gills in relation to feeding habits: a comparative review of marine and freshwater species - Mohamed A. M. Alsafy; Hanan H. Abd-Elhafeez; Ahmed M. Rashwan; Atef Erasha; Safwat Ali; Samir A. A. El-Gendy (BMC Zoology)
Abstract This systematic review highlights the similarities and variations in gill morphology, histology, and anatomical structure between differing fish species. The gill system consists of mainly four pairs of gill arches in most teleost fishes, such as sea bass, sea bream, grouper, and red porgy, etc., while it consists of three pairs of gill arches in pufferfish and striped-red mullet fish. However, Clarias gariepinus had five pairs, including an additional rudimentary fifth-gill arch. The gill structure consisted of gill arches, gill rakers, gill filaments, and secondary lamellae with varied shapes of gill arches such as hook, semilunar, L-shapes, and crescentic shapes. Each gill arch carried mainly two rows of gill rakers, lateral and medial, present in most teleost fishes (Mugil cephalus, Boops boops, Pagrus pagrus, Sparus aurata, European hake, Puffer fish, grey gurnard, sea bass, and sea bream). An additional row appears in Clarias gariepinus or two rows (accessory) in dusky grouper fish. The length and shape of gill rakers are mainly related to feeding habits. The gill rakers in lateral rows are longer, equal, or more in number and more developed than those of the medial rows, except at three gill arches in striped-red mullet fish, the second and third gill arches in pufferfish, and the fourth arch in Pagrus pagrus. gill rakers are absent at the first and second gill arches in Bagrus bayad. The gill arch carries additional structures, such as the air-breathing dendritic organ of the catfish, located in the suprabranchial chamber caudodorsal to the gills and composed of two main parts: small and large ones originated by main stems from the second and fourth-gill arches, respectively. The interbranchial septum can be smooth, form a median crest (seabream), or carry teeth or spines (seabass, pufferfish). Four transversely raised areas on each side are connected by transverse lines caudal to the base of the tongue (Bagrus bayad) and an elevated part at the level of the third-gill arch (Tilapia zilli). Scanning electron microscopy explained the micro-anatomical structures as varied shapes of pavement cells, mucus cell openings, taste buds on the gill arch, varied shapes of grooves or structures and spines near the gill filament side, varied shapes of gill rakers and their spines, and heights in varied feeding types of fish. Histological findings revealed various types of cells, such as superficial pavement cells, large chloride cells, mucous goblet cells, and basal epithelial cells. The lymph space is situated within the gill arch epithelia and is encompassed by cells that resemble tenocytes. The lymph space contains many types of immunological cells, including lymphocytes, granular leukocytes, and rodlet cells. The gill arch comprises sensory structures known as neuromasts and hyaline cartilaginous support. This review underscores the intricate relationship between gill structure and feeding habits across marine and freshwater fishes, highlighting the importance of understanding these variations for ecological, evolutionary, and aquacultural applications and feeding habits.